When the Injury's Healing Process Meets the Needs of a Top-Level Volleyball Player: A Nonconventional Treatment of a Mallet Fracture Reinjury. (February 2019) - Checcarelli, Daniele; Zampolini, Mauro; Berloco, Michele; Fusco, Claudia; Özçakar, Levent
Abstract : Abstract: Managing top-level athlete's recovery after an injury is very complicated because it requires a challenging combination of clinical and social/professional aspects with the need to return as soon as possible to sports play. Herein, we report a top-level volleyball player for whom a finger splint combined with a custom made thermoplastic protection was used for the conservative management of a Mallet fracture reinjury. This way our player continued training and competitions in contrast to conventional rehabilitation protocols, which suggest to avoid new traumas until the healing phase is completed. After 8 wks, we obtained the fracture healing and a complete functional recovery without major medical complications. From our results, we suggest that novel treatment strategies or modification of conventional rehabilitation protocols are worth consideration for the management of high-level sports players' injuries. However, new clinical studies with a larger sample can compare these results with those resulting from both surgical procedures and from immobilization and rest as well. Abstract : Supplemental digital content is available in the text.